Comparative study: synthesis of biodiesel from waste cooking oil using one-step and two-step of transesterification / Nurfazhilah Mohd Johan and Prof Madya Dr Abdul Hadi Zainal - Mohd Johan, Nurfazhilah; Zainal, Abdul Hadi (2020)
Fuel demand is growing while the fossil fuels, cause their degradation and increasing their market value in the world. Climate change and air emissions caused by burning of fossil fuels face the problem with increase the greenhouse effects. So it created by the use of the fossil fuels, the focus had been paid to biodiesel production as alternative way to petrodiesel. Biodiesel is an eco-friendly synthetic diesel fuel that derived from renewable energy generated from the vegetable oil, animal fats and waste cooking oil. The present biodiesel processing process is the transesterification method of the inedible oil with the addition of alcohol and the presence of catalyst to faster the rate of reaction. The transesterification reaction mechanism is highly sensitive to parameters and oil quality such as free fatty acid (FFA) content, density, kinematic viscosity, acid value and flash point. Others parameters that involved in the reaction are temperature, alcohol to oil ratio, concentration catalyst, and reaction time. This research attempts to carry out a comparative study of the transesterification methods (one-step and two-step) for the production of biodiesel from waste cooking oil by analysis 120 journal articles about biodiesel from trusted sources. The optimum parameter for one-step base catalyzed transesterification is temperature at 60˚C with the concentration 1.013 wt.% KOH and molar ratio methanol to oil 6.5:1 for 20 minutes reaction time. For two-step acid base catalyzed transesterification, this method will handled at temperature 58˚C with the molar ratio 10:1 and concentration H2SO4 at 1.0 wt.% for 1 hour 5 minutes the response time.